Evaluating the efficiency of supplementary feeding as a management strategy for enhancing honeybee (Apis mellifera L.) colony growth and productivity - Sultana, Naznin; Reza, Md Elmur; Alam, Md Noor; Siddiquee, Md Nuray Alam; Islam, Md Shafiqul; Rahman, Md Ataur; Sayed, Md Abu; Rahman, Md Mashiur (Frontiers in Bee Science, 2024)
Sustaining honeybee colonies is challenging during dearth periods as their metabolic functions are reduced due to limited foraging activities. The experiment used honeybee colonies of Apis mellifera, and five different low-cost supplementary foods -sugar, banana, pumpkin, maize flour and rice flour syrup -were introduced as treatments. Every box for each treatment received a daily 300 ml supplementary food syrup consisting of a specific amount of feeding materials along with 100 g of brown sugar, and 20 g. The amount of food consumed was assessed on the second day following the supplementation. Supplemental food with low-cost feeding materials significantly impacts the growth and strength of the colonies. Results revealed significant impacts on colony growth and strength, with all supplements contributing to food consumption over 78%. Despite variations in brood and pollen cells, all feeding supplements showcased efficiency in supporting honeybee feeding, indicating their potential utility in mitigating the challenges during the dearth period. Notably, Pumpkin syrup emerged as the best supplement, offering cost-effectiveness compared to sugar and banana syrup, it could reduce sugar syrup costs by 50%, while enhancing brood, honey, and pollen cell production by the percentages of 71.36, 108.36 and 58.73%, respectively. The findings of the economic analysis revealed that the cost of feeding materials was highest for sugar syrup ($1.77), followed by banana ($0.91), pumpkin ($0.83), maize ($0.53), and rice ($0.53). This study suggests that supplementing honeybee colonies with low-cost feeding materials can positively impact colony growth and strength during dearth periods, and advances beekeeper's decisions as a cost-effective alternative to traditional sugar syrup.